2022
DOI: 10.48550/arxiv.2203.11015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Filter Drug-induced Liver Injury Literature with Natural Language Processing and Ensemble Learning

Abstract: Drug-induced liver injury (DILI) describes the adverse effects of drugs that damage liver. Life-threatening results including liver failure or death were also reported in severe DILI cases. Therefore, DILI-related events are strictly monitored for all approved drugs and the liver toxicity became important assessments for new drug candidates. These DILI-related reports are documented in hospital records, in clinical trial results, and also in research papers that contain preliminary in vitro and in vivo experim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Tri-light Warning System for Hospitalized COVID-19 Patients 11 1) Convert the predicted probability to a nonconformity measurement: a metric to quantify how well a particular feature-label combination conforms to the training data. Here, we leveraged a design of the nonconformity measurement α i that has been validated in multiple machine learning applications [34,44]:…”
Section: Reliability Quantification With Conformal Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tri-light Warning System for Hospitalized COVID-19 Patients 11 1) Convert the predicted probability to a nonconformity measurement: a metric to quantify how well a particular feature-label combination conforms to the training data. Here, we leveraged a design of the nonconformity measurement α i that has been validated in multiple machine learning applications [34,44]:…”
Section: Reliability Quantification With Conformal Predictionmentioning
confidence: 99%
“…4) The credibility of the prediction can be computed as the larger P-value [34], which reflects how well the most likely label conform to the distribution of the training data nonconformity measurement. If the credibility is low, the credibility we have for the prediction is low, which may provide us with a flexible tool to tune the policies in medical resource management.…”
Section: Reliability Quantification With Conformal Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that TF-IDF dominates other approaches with respect to the AUROC and AURPC values, suggesting that simple and interpretable approaches could and do, in fact, outperform more sophisticated solutions. In a similar research (Zhan et al, 2022) dedicated specifically to DILI, authors leverage the same text processing techniques like BOW, W2V, and TF-IDF, while instead of D2V, Sentence2Vec is used. In addition, the paper includes the use of Random Forests for particular classification in addition to logistic regression.…”
Section: Introductionmentioning
confidence: 99%